Расчетный выбор параметров электромагнитных экранов сложной пространственной конфигурации - Резинкина, М.М.; Щерба, А.А.; Гринченко, В.С.; Резинкина, К.О. (Технічна електродинаміка, 2012)
Systems, which contain electromagnetic shields with complex shape, have been considered. Numerical relations that allow choosing of electromagnetic shields parameters in dependence on the necessary screening characteristics, have been found. It is shown how to achieve efficient screening of different regions by changing shield's configuration or number of its layers.